IMPROVEMENT OF TECHNOLOGY OF SEWING WOMEN'S BLOUSES SILK FABRIC - Maftunakhon Khoshimova (Western European Studies, 2024)
New assortments of women's blouses were selected and analyzed for effective use in the production of existing silk fabrics of various textures. The models selected for this task were developed and the available silk fabrics were recommended for the manufacture of blouses. The technological process of sewing the product has been developed. It is recommended to introduce the design and working patterns of the blouse in the garment industry.
Keywords: blouse; model; silk; assortment